Cultural Propaganda Exhibitions of the British Council in Ankara in the 1940s - Esra ÖZKAN KOÇ; Raziye Çiğdem ÖNAL (Ankara Araştırmaları Dergisi, 2021)
The axis and allied powers, mainly Germany and Britain, used propaganda in Turkey throughout Second World War in an attempt to persuade Turkey to become an ally. Britain was at the forefront of this movement and held films, conferences, language courses etc at the British Council, which was established in 1934, to promote English language, cultural accumulation, art and architecture. The council, the first office of which was opened in Ankara in 1940, succeeded in strengthening the diplomatic relationships between the two countries by extensively raising public opinion across the country through its activities. Exhibitions, which are a highly effective method of communication for large groups, were organized in the capital Ankara by the British Council during and after Second World War as a vehicle of cultural propaganda to exhibit art and graphics, architecture, educational institutions, books, urbanism, furniture and photography. The pro-British exhibitions provided the opportunity to establish close relations with Turkish Government officials; and so can be seen to have served Britain’s propaganda efforts to secure Turkey as an ally, both during and after the war. Although Britain actually failed to persuade Turkey to become a war ally, these exhibitions carried out by the British Council did succeeded in introducing the English language, culture and lifestyle to the country, and thus creating positive Turkish-British relations even after the war. While the British Council continues to conduct such activities, the exhibitions held by the British Council, which are the subject of the study, are limited to those of the 1940s. The study uses archive documents, news in periodical publications and information obtained from exhibition catalogues to address questions such as the dates of the exhibitions, the areas and works exhibited, the views of the Turkish government, the public, and the press of these exhibitions, as well as the relevance of the exhibitions in their period and how they compared to similar activities by other countries. The study, which is entitled “The Cultural Propaganda Exhibitions of the British Council in Ankara in the 1940’s” and focuses on the exhibition activities organized by the British Council in Ankara during the 10-year period between 1940-1950, concludes that reasons such as the propaganda that occured during World War II, the changing global political balances after the war, and the increasing importance of alliances, all lead the delegation to conduct an intense program of activities in Turkey during those years.